Word of life : introducing Lutheran hermeneutics. - WENGERT, TIMOTHY J. ([Place of publication not identified] AUGSBURG FORTRESS, 2019)
Renowned Reformation scholar Timothy J. Wengert explores the genesis of Lutheran biblical interpretation by tracing the early work of Martin Luther, Melanchthon, and other Wittenberg exegetes. Their new approach led them to view Scripture in terms of "law and gospel," to read and translate the Greek and Hebrew text, and to focus on a theology of the cross and justification by faith. Luther and his colleagues found God working in the last place anyone would reasonably look: on the cross, in weakness and foolishness. Wengert demonstrates how these key historical and theological perspectives can be demonstrated in preaching, reflection, and teaching today. Using brief examples of preaching The Seven Last Word of Christ and reflecting on Luther's work on a variety of Psalms, the author provides a path for students and pastors alike to plumb the depth of Lutheran hermeneutics in their preaching and teaching.
The cloud of witnesses -- Not "just the facts, ma'am" : from definition to effect -- The law always accuses : the Gospel always forgives -- Famous last words -- Living with the saints in the Psalms -- Appendix. Philip Melanchthon on the word 'justification' in 1532.
JSTOR
Keywords: Luther, Martin, -- 1483-1546.; Bible -- Criticism, interpretation, etc. -- History -- 16th century; Bible -- Critique, interprétation, etc. -- Histoire -- 16e siècle.; Luther, Martin, -- 1483-1546; Bible; 1500-1599; Criticism, interpretation, etc; History